Synthesis and decarboxylation of 2,3-Dioxophenylpyrrolidine- 3-carboxylic acid etyhl ester / Julieyana Abdul Manap - Abdul Manap, Julieyana (Faculty of Applied Sciences, 2009)
There were two stage involved in this experiment. The first stage was the synthesis of the 2,3-dioxopyrrolidines and second stage was decarboxylation. In the first stage of synthesis there were three reagents used to produce the ring systems. There were diethyl oxalate, anisaldehyde and an amine. Different amines used were benzylamine and methylamine. The products obtained 1-phenyl-4,5-dioxo-2-pheyl-pyrrolidine-3-carboxylic acid ethyl ester and 1-methyl-4.5-dioxo-2-phenyl-pyrrolidine-3-carboxylic acid ethyl ester respectively. The products were characterized using NMR. In decarboxylation, each product from the first stage was refluxed with 10% HCl for 5 hours and extracted with dichloromethane and ethyl acetate. After drying with anhydrous magnesium sulfate and